2006
DOI: 10.4049/jimmunol.176.1.380
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of TLR4 Signaling by a Novel Adaptor Protein Signal-Transducing Adaptor Protein-2 in Macrophages

Abstract: Signal transducing adaptor protein‐2 (STAP‐2) is a recently identified adaptor protein, that contains pleckstrin and Src homology 2 (SH2)‐like domains as well as a YXXQ motif in its C‐terminal region. Our previous studies have demonstrated that STAP‐2 binds to STAT3 and STAT5, and regulates their signaling pathways. In the present study, STAP‐2 was found to positively regulate LPS/TLR4‐mediated signals in macrophages. Disruption of STAP‐2 resulted in impaired LPS/TLR4‐induced cytokine production and NF‐κB acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 46 publications
2
110
1
Order By: Relevance
“…In this study we demonstrated that STAP-2 interacts with and modifies the function of various signaling or transcription molecules Yamamoto et al, 2003;Sekine et al, 2005Sekine et al, , 2006Sekine et al, , 2007bSekine et al, , 2009a. We also demonstrated that BCR-ABL acts as a novel binding partner for STAP-2 in the presence of both the STAP-2 SH2-like domain and STAP-2 Tyr250 phosphorylation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this study we demonstrated that STAP-2 interacts with and modifies the function of various signaling or transcription molecules Yamamoto et al, 2003;Sekine et al, 2005Sekine et al, , 2006Sekine et al, , 2007bSekine et al, , 2009a. We also demonstrated that BCR-ABL acts as a novel binding partner for STAP-2 in the presence of both the STAP-2 SH2-like domain and STAP-2 Tyr250 phosphorylation.…”
Section: Discussionmentioning
confidence: 60%
“…Its C-terminal region also has a proline-rich region and an YXXQ motif . Previous works in this laboratory found that STAP-2 have the ability to associate with and influence a variety of signaling or transcriptional molecules Yamamoto et al, 2003;Sekine et al, 2005Sekine et al, , 2006Sekine et al, , 2007bSekine et al, , 2009a, including the finding that STAP-2 can modulate the transcriptional activity of STAT3 and STAT5 Sekine et al, 2005), in addition to the FceRI and Toll-like receptor-mediated signals Sekine et al, 2006). Furthermore, thymocytes and peripheral T cells from STAP-2-deficient mice show enhanced interleukin-2 (IL-2)-or T cell receptor-dependent cell growth, integrin-mediated T-cell adhesion and impaired stromal cell-derived factor-1a (SDF-1a)-induced T-cell migration (Sekine et al, , 2007b(Sekine et al, , 2009a.…”
Section: Introductionmentioning
confidence: 98%
“…In this manuscript, we 4 have found that STAP-2 protein is degraded dependently of Casitas B-lineage Lymphoma (Cbl) protein. Cbl is composed of an N-terminal tyrosine-kinase-binding domain, ring-finger motif, a proline-rich region and a C-terminal ubiquitin-associated domain.…”
Section: Introductionmentioning
confidence: 88%
“…For example, STAP-2 interacts with STAT3 through its YXXQ motif [1] and with STAT5 through its PH and SH2-like domains [3], resulted in influencing their transcriptional activity. The SH2-like domain of STAP-2 binds to MyD88 and IKK-a/b, thereby modulating TLR4-mediated cytokine production and NFkB activation [4]. Both the SH2-like domain and the C-terminal proline-rich region of STAP-2 are required for the binding to PLC-g1, and the interaction leads to negative regulation of FceRI-mediated signals [5].…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in Table 1, STAP-2 interacts with, and modulates the function of, several signaling molecules including STAT3/5- Sekine et al, 2005), FcRI- , M-CSFR/c-FMS- and Toll-like receptor-mediated signals (Sekine et al, 2006). STAP-2 interacts with STAT3 through the C-terminal YXXQ motif and enhances STAT3 transcriptional activity.…”
Section: Interacting Proteinsmentioning
confidence: 99%